Pengembangan Media Powtoon Berbasis Model Problem Based Learning Untuk Meningkatkan Penguasaan Konsep Fisika Peserta Didik - Nurmala Hidayah; Muhammad Zuhdi; Muhammad Taufik; Ahmad Harjono (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2021)
The purpose of this study is to determine the validity of developing powtoon media based on problem based learning model to increase understanding of student physics concept. The research design used research and development (R&D) by Thiagarajan with 4d model (define, design, develop, and disseminate). This study is limited only to validity tests by taking the result of expertand practitioner validators and the results of questionnaire responses from students are not conducted limited trials. Limited trials are not conducted due to limitations of time and civility. The validity of powtoon media based on problem based learning model is analyzed using SBi (Ideal Standard Deviation).